Energy–saving analysis in the hydraulic system of loader working device. (3rd December 2012) - Zhang, Weiwei; Zhou, Jun; Zhang, Yanliang; Huang, Panling; Deng, Jianxin
Currently, with the increase of the fuel price, the demands for energy saving technology in construction machinery have been strengthened gradually. Various methods and theories for fuel consumption have been advanced. In this paper, a loader working device used in hydraulic system is built in SimulationX software. Based on the model, the energy saving strategies of the loader are analysed and the hydraulic system of loader working device was proposed to reduce the energy consumption and improve the working efficiency. Through the comparison between simulation and experimental results, several energy saving points can be found by analysing the pressure and flow. Moreover, it is concluded that overflow loss was the main way of power loss in hydraulic system of loader working device.